ANTI-RADIKALISME DALAM KURIKULUM MPI INSTITUT PTIQ JAKARTA - Irfanudin Irfanudin (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2022)
The emergence of cases of violence in every place in the name of religion, is caused by narrow religious fanaticism, without being based on mature religious knowledge, even though the perpetrator is a graduate of a religious college. This study aims to determine the anti-radicalism curriculum at the PTIQ Jakarta Institute. In this study, the author uses a document study, which is a study that focuses on the analysis or interpretation of written material based on its context, while the approach used is a phenomenological approach, which is a type of qualitative research that sees and hears more closely and in detail the explanations and individual understandings of experiences. the experience. The results of this study are an anti-radicalism curriculum at the PTIQ Jakarta institute which is spread over 5 (five) courses, namely the history of Islamic thought, history of Islamic civilization, ulumul Qur'an, interpretation of education and leadership of organizational behavior. The impact of teaching the anti-radicalism curriculum is implemented in the form of student moderation, prioritizing deliberation and making PTIQ Jakarta Institute students have a broad, open and tolerant view